PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 RANAH BATAHAN TAHUN PELAJARAN 2012/2013 - Sanra, Fefri; Nasution, Minora Longgom; K, Delsi. (STKIP PGRI Sumbar, 2013)
In this research , as background of the study is low achievement of student in SMPN 1 Ranah Batahan. The purpose of study is to determine: whether are the result of using cooperative type Think Pair Share is better than using the conventional learning in the teaching process. The kind of study is experimental research. Population of the study was VIII grade of SMPN 1 Ranah Batahan especially academic years 2012/2013. The researcher chosen the sample by using random sampling technique, the samples were VIII.3 and VIII.1. In collecting data, the researcher used the instrument by giving achievement test. The test is essay form that has reliability about = 0,89. In addition, analyzing data that had been done by using t test. Based on the hypothesis testing is gotten P-value = 0,010 < . In this case, the hypothesis can be received. It can be concluded that using cooperative type of the Think Pair Share is better than using conventional learning in teaching process.